Health Monitoring KIOSK: An effective system for ru ral health management - Rajalaxmi Das; Himansu Mohan Padhy (International Journal of Innovations in Engineering Research and Technology, 2021)
In the rural areas of our country, patients went tothe public health centers (PHC) for their treatment. PHCsin India are allotted with hardly one doctor. It isreally difficult at a single doctor’s end to provide treatmentto huge number of patients approaching a single doctor. Therefore, in this work it is proposed to develop anautomated diagnosis system by developing a Health KIOSK.